Benzophenone-based small molecular cathode interlayers with various polar groups for efficient polymer solar cells. Issue 21 (17th May 2017) - Liu, Zhiyang; Li, Wang; Peng, Ruixiang; Jiang, Weigang; Guan, Qian; Lei, Tao; Yang, Rongjuan; Islam, Amjad; Wei, Qiang; Ge, Ziyi
Abstract : A series of novel benzophenone-based molecules with different polar groups as cathode interfacial materials were synthesized for polymer solar cells. Abstract : A series of novel benzophenone-based small molecular cathode interfacial materials with different polar groups including hydroxyl groups, neutral amino groups, amino N -oxide, and sulfobetaine ions were synthesized for PTB7:PC71 BM-based polymer solar cells between the active layer and Al electrode. The photovoltaic properties of the devices with these interfacial materials were studied. The differences in interface modification performance of hydroxyl and amino interfacial materials were investigated for the first time. The devices with a solution-processed amino N -oxide-based interlayer showed a PCE of 9.34% with the highest short-circuit current density and fill factor by reducing the series resistance and charge recombination compared to the devices with the other interlayers in this work. The study of structure–property relationships proposes the significant guidance for the design of efficient cathode interface materials in organic solar cells.